The Nuosu Book of Origins : A Creation Epic from Southwest China - Zopqu, Jjivot; Aku, Wuwu, 1964-; Bender, Mark; Project Muse. (Seattle : University of Washington Press, 2019)
"The Nuosu people, who were once overlords of vast tracts of farmland and forest in the uplands of southern Sichuan and neighboring provinces, are the largest division of the Yi ethnic group in southwest China. Their creation epic plots the origins of the cosmos, the sky and earth, and the living beings of land and water. This translation is a rare example in English of indigenous ethnic literature from China. Transmitted in oral and written forms for centuries among the Nuosu, The Book of Origins is performed by bimo priests and other tradition-bearers. Poetic in form, the narrative provides insights into how a clan- and caste-based society organizes itself, dictates ethics, relates to other ethnic groups, and adapts to a harsh environment. A comprehensive introduction to the translation describes the land and people, summarizes the work's themes, and discusses the significance of The Book of Origins for the understanding of folk epics, ethnoecology, and ethnic relations"--
Genealogy of sky = Momu cy -- Genealogy of earth = Mudde cy -- Transformation of sky and earth = Momu zzyqo cy -- Genealogy of lightning = Murzyr cy -- Separation of sky and earth = Muvu mudie po -- Great bimo = Awo shubu -- Genealogy of spirit monkey = Anyu ddussy cy -- Zhyge alu = Zhyge alu -- Shooting down suns and moons = Gge nbie hle nbie -- Calling out single sun and single moon = Gge di hle di gu -- Twelve branches of snow = Vonre sse cinyi -- Genealogy of Shyly Wote = Shyly wote ssy -- Ozzu (Tibetan) lineages = Ozzu cy -- Ozzu (Tibetan) migrations = Ozzu muche -- Hxiemga (Han) people's lineage = Hxiemga cy -- Hxiemga (Han) people's migrations = Hxiemga muche -- Foreigner's lineage = Yiery cy -- Migrations of foreigners = Yiery muche -- Nuosu lineages = Nuosu cy -- Emperor vomu and ni and vi genealogies = Vomu ni vi cy -- Genealogy of Ahuo = Ahuo cy -- Migration of ahuo = Ahuo muche -- Genealogy of Nzy clan = Nzyzzur pu -- Highpoints of migrations of the Ggu Ho = Gguho cy bo -- Migrations of Qonie = Qonie cy bo -- Changes in Hxuo villages = Hxuoqo hxeqo -- Genealogy of Gguho = Gguho cy -- Migrations of nine sons of Gguho Durzhy Ddiwo = Kurdie Gguho Durzhy Ddiwo Wo Sse Ggu cy -- Genealogy of Qoni = Qoni cy.
Translated from the Nuosu.
Description based on print version record.
Keywords: Yi (Chinese people); Mythology, Chinese; Folk poetry, Yi; Creation -- Mythology; RELIGION / Comparative Religion; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; Creation -- Mythology -- China, Southwest; Mythology, Chinese; Yi (Chinese people) -- Folklore; Folk poetry, Yi -- China, Southwest -- Translations into English; Southwest China; Translations; Folklore; Electronic books